Spirochromone-chalcone conjugates as antitubercular agents: synthesis, bio evaluation and molecular modeling studies - Mujahid, Mohammad; Perumal, Yogeeswari; Sriram, D.; Basavanag, U. M. V.; Dıaz-Cervantes, Erik; Cordoba-Bahena, Luis; Robles, Juvencio; Gonnade, Rajesh Ghanshyam; Karthikeyan, Muthukumarasamy; Vyas, Renu; Krishnan, M. Muthu (RSC Advances, 2015)
A new series of spirochromone annulated chalcone conjugates were synthesized and evaluated for their antitubercular activity against Mycobacterium tuberculosis H37Rv strain. These compounds were subjected to molecular modeling studies using docking and chemoinformatics based approaches. The docking simulations were performed against a range of known receptors for chalcone derived compounds to reveal MTB phosphotyrosine phosphatase B [MtbPtpB] protein as the most probable target based on the high binding affinity scores. Five compounds exhibit significant inhibition, showing minimum inhibitory concentration values i.e. MIC values ranging from 3.13–12.5 μg mL−1. Further analysis of the synthesized compounds with known and in-house developed chemoinformatics tools unequivocally established their potential as anti-tubercular compounds. QSAR modeling revealed a quantitative relationship between biological activities and frontier molecular orbital energies of synthesized compounds. The predictive model can be employed further for virtual screening of new compounds in this series.

Structural insights into the hydrogen-bonding and folding pattern in ant-ant-pro-gly tetrapeptides - Baravkar, Sachin B.; Kotmale, Amol S.; Mobin, Samir R.; Gonnade, Rajesh Ghanshyam; Sanjayan, Gangadhar J. (European Journal of Organic Chemistry, 2017)
In this paper, we provide structural insights into the hydrogen-bonding and folding pattern in Ant-Ant-Pro-Gly tetrapeptides (Ant: anthranilic acid; Pro: proline; and Gly: glycine). Comparison of the C-terminal esters and their amide analogs revealed strikingly different H-bonding networks. Whereas the ester analogs displayed an open structure without terminal H-bonding interactions, the amide analogs showed a completely folded structure. Structural details were revealed by using a combination of X-ray crystal structure studies and NOE-based molecular dynamics (MD) simulation studies.

Synthesis of annulated bis-indoles through Au(I)/brønsted acid-catalyzed reactions of (1H-indol-3-yl)(aryl)methanols with 2-(arylethynyl)-1H-indoles - Patil, Nitin T.; Inamdar, Suleman M.; Gonnade, Rajesh Ghanshyam (Organic & Biomolecular Chemistry, 2017)
A general method to access annulated bis-indoles from (1H-indol-3-yl)(aryl)methanols and 2-(arylethynyl)-1H-indoles under the catalysis of the Ph3PAuOTf/Brønsted acid binary catalyst system has been developed. The reaction was found to proceed in a highly efficient manner and benefit from easy-to-make starting materials, broad substrate scope and operational simplicity. The potential of this method has also been exemplified for the synthesis of pyrrole-annulated indoles using 2-(phenylethynyl)-1H-indoles and phenyl(1H-pyrrol-2-yl)methanols. Furthermore, the use of a ternary catalyst system, involving PdCl2/Brønsted acid/Ph3PAuOTf catalysts, has been realized for the synthesis of annulated bis-indoles starting directly from 2-(phenylbuta-1,3-diyn-1-yl)aniline and (1H-indol-3-yl)(aryl)methanol. Mechanistically, this reaction is very interesting since the overall process involves three different catalytic cycles catalyzed by three different catalysts in a relay fashion.